1998
DOI: 10.1144/gsl.sp.1998.131.01.16
|View full text |Cite
|
Sign up to set email alerts
|

Collision-related break-up of a carbonate platform (Eratosthenes Seamount) and mud volcanism on the Mediterranean Ridge: preliminary synthesis and implications of tectonic results of ODP Leg 160 in the Eastern Mediterranean Sea

Abstract: Drilling of the Eratosthenes Seamount south of Cyprus documented incipient collision of the African and Eurasian plates. The oldest sediments recovered, mid?-Cretaceous shallow-water limestones, are overlain by Upper Cretaceous to Lower Oligocene pelagic carbonates, with several hiatuses. Following uplift, a carbonate platform was established in the Miocene; Eratosthenes was then below eustatic sea level during the Messinian desiccation crisis. The platform subsided to bathyal depths during the Lower Pliocene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 37 publications
1
23
0
Order By: Relevance
“…The activity of mud volcanoes in the Alboran Sea seems to be episodic as observed in other Mediterranean settings, e.g., the Mediterranean Ridge in the eastern basin (Robertson and Ocean Drilling Program Leg 160 Scientific Party, 1996;Robertson et al, 1998) and recurrent over timescales of thousands of year. Recent extrusive activity in the Southern MV Field started earlier than 16 ka BP, while the age of the last extrusive episode differs among the studied MVs by thousands of years (from >15.6 ka at Maya to >0.27 ka at Carmen).…”
Section: Recent Volcanic Activitymentioning
confidence: 78%
“…The activity of mud volcanoes in the Alboran Sea seems to be episodic as observed in other Mediterranean settings, e.g., the Mediterranean Ridge in the eastern basin (Robertson and Ocean Drilling Program Leg 160 Scientific Party, 1996;Robertson et al, 1998) and recurrent over timescales of thousands of year. Recent extrusive activity in the Southern MV Field started earlier than 16 ka BP, while the age of the last extrusive episode differs among the studied MVs by thousands of years (from >15.6 ka at Maya to >0.27 ka at Carmen).…”
Section: Recent Volcanic Activitymentioning
confidence: 78%
“…Previous studies of the Pleistocene of southern Cyprus, including evidence from shallow-marine and continental sediments and geomorphic erosion surfaces, have indicated that strong surface uplift of the Troodos ophiolite took place, beginning in the upper Pliocene (Robertson, 1977;McCallum and Robertson, 1990;Houghton et al, 1990;Poole and Robertson, 1991). The results of Leg 160, following geophysical surveys (Limonov et al, 1994;Robertson et al, 1995a), suggest that the overall driving force of the uplift of the Troodos ophiolite was the collision of a continental fragment, the Eratosthenes Seamount, with the active boundary of the Eurasian and African plates (i.e., the Cyprus active margin) located directly south of Cyprus (Robertson et al, 1995a, b;Emeis, Robertson, Richter, et al, 1996;Fig. 1).…”
Section: Introductionmentioning
confidence: 91%
“…Cretaceous and Eocene microfossils are also present, but these are reworked together with younger microfossils within the clasts (Emeis, Robertson, Richter, et al, 1996;Robertson et al, 1996). Additional material recovered from different volcanoes in the Olimpi field during TREDMAR cruises (Limonov et al, 1994 also yielded nannofossils and pelagic foraminifers of mainly Miocene age, with some Pliocene, Oligocene, and rare Cretaceous forms, many of which were also reworked (Premoli-Silva et al, 1996).…”
Section: Age Of Clastsmentioning
confidence: 97%
“…In this synthesis, we will first summarize key post-cruise results that supplement initial shipboard studies of the mud volcanoes (Emeis, Robertson, Richter, et al, 1996;Robertson et al, 1997;Kopf et al, in press). We will then outline current knowledge of the present-day tectonic setting of the Mediterranean Ridge accretionary complex in relation to mud volcanism, and go on to discuss the Mesozoic-Holocene tectonic development of the southerly Neotethyan basin in which the mud volcanoes developed.…”
Section: Introductionmentioning
confidence: 99%